Preadmission antipyretics in Reye's syndrome. Issue 7 (July 1988) - Hall, S M; Plaster, P A; Glasgow, J F; Hancock, P
Abstract : The parents of 106 children who had had Reye's syndrome and those of 185 comparison children who had febrile illnesses were interviewed in order to compare preadmission medication exposure rates in the two groups. Although comparable proportions of case and comparison patients had taken antipyretics in the three weeks before admission, a significant excess of cases (59% compared with 26% in the comparisons) had been given aspirin, whereas significantly more comparison children (49% compared with 25% in the cases) had taken paracetamol. There was an excess exposure to aspirin in children under 5 years of age; the excess observed in older patients just failed to reach significance. Separate analyses within Northern Ireland and England also showed a case-comparison difference. A significant correlation was shown between aspirin (but not paracetamol) exposure and the closeness with which cases conformed to the diagnostic criteria of Reye's syndrome, measured by an artibrary score. The many difficulties of conducting and interpreting the findings of an epidemiological risk factor study of an association between aspirin and Reye's syndrome are reviewed and emphasised. Inherent biases were present in this as in previous studies and it did not conform to the classical case-control design. Nevertheless the findings suggested that an association between Reye's syndrome and preadmission aspirin may exist in some children.